Learning discriminative activated simplices for action recognition - Luo, Chenxu; Ma, Chang; Wang, Chunyu; Wang, Yizhou (Conference on Artificial Intelligence (AAAI), 2017)
We address the task of action recognition from a sequence of 3D human poses. This is a challenging task firstly because the poses of the same class could have large intra-class variations either caused by inaccurate 3D pose estimation or various performing styles. Also different actions, eg, walking vs. jogging, may share similar poses which makes the representation not discriminative to differentiate the actions. To solve the problems, we propose a novel representation for 3D poses by a mixture of Discriminative Activated Simplices (DAS). Each DAS consists of a few bases and represent pose data by their convex combinations. The discriminative power of DAS is firstly realized by learning discriminative bases across classes with a block diagonal constraint enforced on the basis coefficient matrix. Secondly, the DAS provides tight characterization of the pose manifolds thus reducing the chance of generating overlapped DAS between similar classes. We justify the power of the model on benchmark datasets and witness consistent performance improvements.